Genomic analysis of Pseudomonas sp. GWSMS-1 isolated from Antarctica reveals its potential in Chitin hydrolysis - Haiyu Zeng; Zheng Wang; Jianjun Wang; Yong Yu; Wei Luo; Huirong Li; Haitao Ding (BMC Genomic Data)
Abstract Objectives The degradation products of chitin exhibit various biological activities, giving them significant application potential. Chitinase-producing bacteria can be isolated from diverse environments such as soil, natural waters, and rhizospheres. However, their chitinolytic activity is often limited, particularly at low temperatures. Data description In this study, complete genome sequencing of a cold-adapted chitinolytic Pseudomonas strain, GWSMS-1, revealed a 4,606,781-bp linear chromosome with a G+C content of 59%. The genome encodes 4,599 protein-coding genes, 73 tRNA genes, and 27 rRNA genes. Functional annotation through GO, KEGG, and CAZy databases identified a substantial number of chitinase-encoding genes, which likely contribute to its high chitin-degrading capacity. The genomic insights into GWSMS-1 highlight its potential for applications in chitin degradation and offer valuable gene candidates for further research.